2009
DOI: 10.1128/mcb.00032-09
|View full text |Cite
|
Sign up to set email alerts
|

RelB NF-κB Represses Estrogen Receptor α Expression via Induction of the Zinc Finger Protein Blimp1

Abstract: Aberrant constitutive expression of NF-B subunits, reported in more than 90% of breast cancers and multiple other malignancies, plays pivotal roles in tumorigenesis. Higher RelB subunit expression was demonstrated in estrogen receptor alpha (ER␣)-negative breast cancers versus ER␣-positive ones, due in part to repression of RelB synthesis by ER␣ signaling. Notably, RelB promoted a more invasive phenotype in ER␣-negative cancers via induction of the BCL2 gene. We report here that RelB reciprocally inhibits ER␣ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
73
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(80 citation statements)
references
References 65 publications
5
73
0
Order By: Relevance
“…Transrepression of ER by NF-kB has been proposed as a mechanism by which ER-positive breast tumor cells lose ER expression and, hence, gives rise to a subpopulation of tumor cells that are resistant to endocrine treatment (38,39). Furthermore, we provide evidence that increased NF-kB signaling leading to ERa alterations are mediated via RRM2 overexpression and can be reversed using didox through its ability to inhibit NF-kB activation (Fig.…”
Section: Discussionmentioning
confidence: 52%
“…Transrepression of ER by NF-kB has been proposed as a mechanism by which ER-positive breast tumor cells lose ER expression and, hence, gives rise to a subpopulation of tumor cells that are resistant to endocrine treatment (38,39). Furthermore, we provide evidence that increased NF-kB signaling leading to ERa alterations are mediated via RRM2 overexpression and can be reversed using didox through its ability to inhibit NF-kB activation (Fig.…”
Section: Discussionmentioning
confidence: 52%
“…Among them, PRDM1 that encodes the transcriptional repressor Blimp-1 28 was recently described as a potent repressor of ER-α synthesis, which is induced by activation of the NFκB member RelB, leading to a migratory phenotype. 29 Moreover, Blimp1 is emerging as a crucial downstream effector of RelB/Bcl-2/ Ras pathway that promotes EMT signature and breast cancer cell migration. 30 In addition, we observed increased expression of ITPKA and HEY1 genes previously described to promote cell motility, EMT, and migration.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, activation of NF-κB by inflammation may negate the effect of its suppression by ERα, which ultimately induces a more aggressive breast cancer phenotype. It has also been shown that NF-κB can suppress ERα activity in several experimental models (Bodine et al, 1999; Feldman et al, 2007; Wang et al, 2009). NF-κB and ERα can also synergistically induce expression of target genes which are involved in inflammation (Frasor et al, 2008), apoptosis (Stanculescu et al, 2010; Pradhan et al, 2012), proliferation (Tu et al, 2006) and drug-resistance (Pradhan et al, 2010).…”
Section: Inflammation As a Promoter For More Aggressive Erα+ Breasmentioning
confidence: 97%